2020
DOI: 10.1111/sltb.12671
|View full text |Cite
|
Sign up to set email alerts
|

Capability for suicide: Discrimination as a painful and provocative event

Abstract: Objective Developing the capability to die by suicide, and overcoming one's natural instinct of self‐preservation, is thought to occur as a result of habituation to the fear and pain surrounding suicide. However, investigations of suicide capability have yet to examine whether perceived discrimination serves as a painful and provocative event that contributes to capability for suicide. The purpose of the current study was to examine the association of perceived discrimination and suicide capability for Black a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…Suicide is the third leading cause of death among Black youth ages 15−24 and is on the rise (Brooks et al, 2020). Racial discrimination, a pervasive psychosocial stressor experienced by the vast majority of U.S. Black youth (Pachter et al, 2018), predicts Black youths' capacity for suicide above and beyond non-discriminatory stressors (Brooks et al, 2020). It is increasingly urgent to understand the underlying mechanisms by which discrimination deteriorates mental health.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Suicide is the third leading cause of death among Black youth ages 15−24 and is on the rise (Brooks et al, 2020). Racial discrimination, a pervasive psychosocial stressor experienced by the vast majority of U.S. Black youth (Pachter et al, 2018), predicts Black youths' capacity for suicide above and beyond non-discriminatory stressors (Brooks et al, 2020). It is increasingly urgent to understand the underlying mechanisms by which discrimination deteriorates mental health.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…This review found stronger evidence of an association between indirectly and directly self-damaging behaviors (e.g., engaging in non-suicidal self-injury, previous suicide attempts) and acquired capability ( May & Victor, 2018 ). A more recent study found that for Black (but not White) adults, discrimination was associated with increased capability for suicide ( Brooks et al, 2020 ), suggesting a potentially important route through which members of stigmatized groups may acquire the capability for suicide.…”
Section: Introductionmentioning
confidence: 99%
“…A few of the events that do constitute potential triggers of acquired capability are known to be elevated among SGM people (e.g., experienced or witnessed physical/sexual abuse), yet there is no distinction on the PPES delineating whether or not someone experienced or witnessed abuse motivated by identity-specific bias. Further, there are no events on the PPES that inquire about exposure to discrimination despite clear and consistent evidence that discrimination is a precursor to suicide attempts among SGM people ( Clements-Nolle et al, 2006 ; Layland et at., 2020 ) and is associated with acquired capability among minority adults ( Brooks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, theories of suicide largely neglect how structural inequality, colonization, and intersecting systems of oppression, privilege, and power shape vulnerability to suicide. Though there have been some exiting new efforts to theorize how structural inequality and intersectionality matter to suicidology (Brooks et al, 2020;Opara et al, 2020;Standley, 2020), much more work is needed. Based on broader research within the sociology of mental healthwhich does take up this issue -the patterns are likely to be complex and again not distillable to individual experiences with discrimination or prejudice (McLeod, 2015;Williams et al, 2019;Laster Pirtle, 2020).…”
Section: Future Directionsmentioning
confidence: 99%